Spatial Analysis - Time of Stolen Crimes in District 12 of Tehran - nabi moradpoor; keramatolah zayyari (تحقیقات کاربردی علوم جغرافیایی)
Spatial Analysis of Crimes at Different Hours of the Day, the Days of the Week, Month, and Seasons is an Effective Way to Control and Prevent Urban Crime. These analyzes give city management and other city safety officials, including law enforcement officials, the possibility to take preventive measures to eliminate or mitigate the effects of these factors in the city. The purpose of this study was to investigate the spatial analysis of theft crimes on a daily, weekly, monthly and seasonal basis in the 12th metropolitan area of Tehran. The research method in this article is descriptive-analytic. The comprehensive statistical data included the statistical blocks of 1390 in the neighborhoods of the 12th district of Tehran and the crimes related to theft in 2010. The most important statistical tests used are the Center-Medium and Oval-standard deviation tests, and from among the clustering tests, the nearest neighbor index is used to identify massive cores. The results of this study indicate that 446 crimes related to theft, Ferdowsi and Lalehzar neighborhoods, and Sa'di Baharestani have the most crimes and minorities in Kosar and Mokhtari. The pattern of distribution of crimes in the 12th region is clustered and the most important crustal focal points are formed at the intervals of the Shemiran, Iran, Baharestan - Saadi, Ferdowsi -Laleh Zar, Arg Pamenar, Imamzadeh Yahya and the Cascade. The spatial analysis of stealing crimes also suggests that the direction and extent of theft is different at different times of the day, weekdays, and on a monthly basis.